Amazon S3 Essentials. - Gulabani, Sunil (Packt Publishing, 2015)
Get started with Amazon S3 for virtually unlimited cloud and Internet storageAbout This Book Familiarize yourself with the concepts of Amazon S3 Understand basic operations of bucket, folders, and objects using Amazon S3 SDK Java Leverage the power of Amazon S3 to effectively store and retrieve dataWho This Book Is For This book is intended for System Engineers/ Developers, Software Architects, Project managers, and users who want to explore Amazon S3 SDK Java. If you want to learn about Amazon S3 quickly, then this book is for you. Basic knowledge of Java programming is expected. What You Will Learn Start with the basic concepts of Amazon S3 to get you going Use Copy Object and Multipart Copy Object for objects of different sizes Understand how to use the amazon management console for Amazon S3 Learn how to use the AWS SDK of Java and consume the Amazon S3 Get to grips with managing the bucket life cycle Configure CORS to share resources to a different domain Discover how to develop and deploy the static website on Amazon S3 using different services of AmazonIn Detail Amazon Simple Storage Service (Amazon S3), provides developers and IT teams with secure, durable, and highly-scalable object storage. Amazon S3 is easy to use, with a simple web services interface to store and retrieve any amount of data from anywhere on the web. S3 is automatically web scalable and responds to the requirements of your application and traffic, and therefore offers a key element to help companies deal dynamically with any spike in traffic for their application (such as a free e-book offer). This book starts with the basics of the Amazon S3 and its features, and you will quickly get an understanding how to use the Amazon Management Console for Amazon S3 which is the simplest way to manage Amazon S3. Next, we will cover basic operations on bucket, folder, objects. Once the basic operations are understood, you will know how to use Amazon S3 using Java SDK. Following that, you will learn about Copy Objects and Multipart copy objects for large objects size. You will also learn to manage the life cycle of bucket and how to share resources to the different domain by configuring CORS. The book will then guide you through the development and deployment of a static website on Amazon S3 using different services of Amazon. By the end of the book, you will be able to create a scalable application using Amazon S3. Style and approach This fast-paced book is a pragmatic guide to writing Amazon S3 applications. Each chapter is blended beautifully with lucid concepts and pertinent examples.
Print version record.
Added to collection customer.56279.3
Keywords: Amazon.com (Firm); Amazon.com (Firm); Cloud computing; Web services; Cloud computing; Web services; Electronic books